Proposal for joint assessment in secondary science in the Eastern Caribbean teachers' colleges - King, Winston K. (School of Education, UWI, 1983)
This is a draft syllabus for the training of secondary science teachers in the Eastern Caribbean, which was developed by science tutors from various colleges in the region. It includes an assessment procedure and a rationale. The two-part assessment procedure is detailed--a college-based continuous assessment (40 percent) and a School of Education-based examination (60 percent). A Draft Syllabus for Secondary Teacher Training Course (Science) is outlined
Keywords: Eastern Caribbean